2020
DOI: 10.5267/j.msl.2020.3.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting online purchase intention: A study of Vietnam online customers

Abstract: The paper examines factors influencing online purchase intention of Vietnamese. Based on the Unified Theory of Acceptance and Use of Technology (UTAUT), the study develops a theoretical model including four explanatory variables of online purchase intention: performance expectancy (PE), social influence (SI), effort expectancy (EE) and facilitating conditions (FC). The empirical results obtained in a sample of 204 valid interviewees reveal the statistically significant and concurrent impact of the mentioned de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 8 publications
0
21
0
10
Order By: Relevance
“…Karpavičius and Yu (2019) found that external growth opportunity is directly associated with higher equity policy of the firms while the inverse is true in the case of higher debt to equity ratio. Similarly Doan (2020) and Fan (2019) they concluded that the firms in order to grow dependence on debt financing must be reduced as compared to equity financing. Tran, Walle, and Herwartz (2020) used a heteroscedasticitybased identification strategy to investigate the impact of firm size, local financial development, and corruption on growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Karpavičius and Yu (2019) found that external growth opportunity is directly associated with higher equity policy of the firms while the inverse is true in the case of higher debt to equity ratio. Similarly Doan (2020) and Fan (2019) they concluded that the firms in order to grow dependence on debt financing must be reduced as compared to equity financing. Tran, Walle, and Herwartz (2020) used a heteroscedasticitybased identification strategy to investigate the impact of firm size, local financial development, and corruption on growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2 2020). A lack of online purchase intent is a significant stumbling block to e-commerce growth and has a significant impact on online business (Doan, 2020;He et al,2008).…”
Section: Business Management and Strategymentioning
confidence: 99%
“…In other words, they are influenced by their relatives, friends, and their trusted person when purchasing fashion products on cross-border e-commerce websites. Doan (2020), claims that customers generally believe the reviews and ratings left by friends and family who have made online purchases. Those who are apprehensive to shop online may find their circles' opinions are important regardless of their subjectiveness.…”
Section: Practicalmentioning
confidence: 99%
“…Online purchase intention is defined as a person's condition when someone has the desire and interest to buy a product or use certain services on an application or web (Liat et al, 2014). In this study, there are four dimensions to explain online purchase intention variables, namely performance expectancy, effort expectancy, social influence, and facilitating conditions (Doan, 2020). Consumer behavior is a measure that is directly involved in obtaining, consuming, and disposing of a product or service, including the process of finding out about the product to owning it (Doan, 2020).…”
Section: Introductionmentioning
confidence: 99%